Otentisitas Kepemimpinan dan Kepercayaan Karyawan dengan Mediasi Perilaku Kewarganegaraan Merek terhadap Keterlibatan Pelanggan - Rosmayadi, Yudi; Amalia, Dinda (Awatara Publisher, 2026)
This study investigates the influence of leadership authenticity on customer engagement through the mediating roles of employee trust and brand citizenship behavior in the hospitality industry. Grounded in Brand Citizenship Behavior Theory, the research examines how authentic leadership contributes to customer engagement by fostering trust-based relationships and encouraging employees to perform voluntary brand-supportive behaviors. A quantitative approach was employed using a cross-sectional survey design. Data were collected from 287 employees working in three-star and four-star hotels in Purwakarta, West Java, Indonesia. The data were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM). The findings reveal that leadership authenticity positively influences employee trust and brand citizenship behavior. Employee trust also significantly enhances brand citizenship behavior, while brand citizenship behavior positively affects customer engagement. Furthermore, the mediation analysis confirms that brand citizenship behavior significantly mediates the relationship between leadership authenticity and customer engagement. The results also demonstrate a significant sequential mediation effect of employee trust and brand citizenship behavior between leadership authenticity and customer engagement. These findings suggest that authentic leadership contributes to customer engagement indirectly through the development of trusting employee relationships and discretionary brand-supportive behaviors. The study extends the application of Brand Citizenship Behavior Theory by integrating leadership and customer engagement perspectives and provides practical implications for strengthening internal branding strategies within service organizations.